Pendekatan Open Innovation Pada Usaha Virgin Coconut Oil (VCO) “Indococo” Oleh CV.Emka Indococo Sejahtera Di Kelurahan Sarongsong I Kecamatan Airmadidi Kabupaten Minahasa Utara - Tedjo, Otniel Matheau Anggoro; Rengkung, Leonardus Ricky; Tangkere, Ellen Grace (AGRI-SOSIOEKONOMI, 2023)
This study aims to identify open innovation practice on SMEs with focus on CV. Emka Indococo Sejahtera that produce VCO “Indococo” located in Kecamatan Airmadidi on North Minahasa Regency. This study was conducted from August to November 2022. Using primary data by collected through interviews with inventor of VCO “Indococo” i.e. Prof. Dr. Ir. Lucia C. Mandey, MS and used secondary data collected through Google Scholar such as books, journal article and literature reviews. Identification results showed that open innovation has applied on CV. Emka Indococo Sejahtera as their business strategy. With their position on topdown, strategically-driven, distributed activities, open innovation practices by CV. Emka Indococo Sejahtera showed that their business activities as a strategy related to open innovation activities so there is an encouraged to developed and more exploration open innovation implementation as a strategy to survive in the market in the future.